Personality Traits Related to Binge Drinking: A Systematic Review - Adan, Ana; Forero, Diego A.; Navarro, José Francisco (Frontiers in Psychiatry, 2017)
The pattern of alcohol consumption in the form of binge drinking (BD) or heavy episodic drinking has increased notably worldwide in recent years, especially among adolescent and young people, being currently recognized as a global health problem. Although only a minority of binge drinkers will develop a substance use disorder, BD may have negative personal and social consequences in the short and medium term. The objective of this paper is to review the findings on personality traits related to binge drinkers and to emphasize the aspects that should be examined in order to make progress in this area. The main characteristics of personality related to the practice of BD, regardless of the theoretical model used, are high Impulsivity and high Sensation seeking, as well as Anxiety sensitivity, Neuroticism (Hopelessness), Extraversion and low Conscientiousness. The data obtained may have theoretical implications to elucidate the endophenotype of BD, but they are especially useful for their preventive applications. Integration into prevention programs of emotional self-control skills, decision-making, social skills and strategies to manage negative emotions, will minimize the risk factors or consequences of BD associated with personality and will improve their effectiveness. In the future, it is necessary to harmonize a common measurement instrument for the assessment of personality, develop longitudinal studies with large samples that also integrate biological and neurocognitive measurements, and determine the reciprocal relationship between personality and BD together with its modulating variables, as well as the possible cultural differences.